2017
DOI: 10.3390/ma10121419
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, Thermodynamic and Electronic Properties of Wurtzite and Zinc-Blende GaN Crystals

Abstract: For the limitation of experimental methods in crystal characterization, in this study, the mechanical, thermodynamic and electronic properties of wurtzite and zinc-blende GaN crystals were investigated by first-principles calculations based on density functional theory. Firstly, bulk moduli, shear moduli, elastic moduli and Poisson’s ratios of the two GaN polycrystals were calculated using Voigt and Hill approximations, and the results show wurtzite GaN has larger shear and elastic moduli and exhibits more obv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 66 publications
5
26
0
1
Order By: Relevance
“…H v = 0.92(B/G) 1.3137 G 0.708 (10) It is reported that materials with Vickers hardness larger than 40 GPa can be classified as superhard materials [45]. For the calculated value of H v of Ni 3 Al is 54.004 GPa, it is supposed that N 3 Al and N 3 Al-based materials have an excellent ability to resist being scratched or dented.…”
Section: Elastic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…H v = 0.92(B/G) 1.3137 G 0.708 (10) It is reported that materials with Vickers hardness larger than 40 GPa can be classified as superhard materials [45]. For the calculated value of H v of Ni 3 Al is 54.004 GPa, it is supposed that N 3 Al and N 3 Al-based materials have an excellent ability to resist being scratched or dented.…”
Section: Elastic Propertiesmentioning
confidence: 99%
“…For example, the bulk modulus of L1 2 -ordered Ni 3 Al explored by Pearson et al is 229.2 GPa [8] while the value obtained by Yasuda et al is 171.0 GPa [9]. In order to break through the limitation derived from experimental methods, in recent years, first principles calculations have been successfully conducted to calculate the elastic properties of alloys and intermetallics [10][11][12][13][14]. Based on first principles, Wen et al [1] calculated the bulk modulus and Young's modulus of Ni 3 Al, as well as the effects of pressure on the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, GGA overestimates the lattice parameters while LDA underestimates them, and the lattice parameters obtained from LDA are much closer to experimental data. Our previous work revealed that, compared to GGA, LDA is more accurate in predicting elastic properties [38]. Therefore, LDA was applied in the following study.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…Нитрид галлия (GaN) в настоящее время широко применяется для производства устройств силовой и оптоэлектроники и вызывает огромный интерес у исследователей. Несмотря на большой объем накопленных сведений о свойствах GaN [1,2], все еще остаются недостаточно изученными его упругие и пластические свойства. Это связано с тем, что для достоверности таких исследований требуются достаточно крупные образцы, которые в силу ряда причин были ранее недоступны.…”
Section: Introductionunclassified